Perceptions of the results of cooperation with rivals - the perspective of Danish, Japanese and Polish companies. Does the cultural background matter? - Jankowska, Barbara; Bartosik-Purgat, Małgorzata (Economics and Business Review, 2012)
Doing business internationally, it is crucial for the companies to contact, cooperate and communicate with foreign partners. There are many differences between partners (companies) coming from different countries and cultures. Sometimes we do not take into account the importance of these aspects and do not consider such differences during the initial stages of cooperation. The authors would like to underline the problem of cultural differences among companies coming from other markets and different parts of the world. The aim of the paper is an attempt to investigate the implications of coopetition for companies coming from three different cultures. The research question is whether the companies coming from relationship-focused societies perceive cooperation with rivals as more important for their success assessed with the use of measures of international competitiveness and internationalization. The empirical part of the paper shows the research into the results of coopetition for enterprises from three different cultures, conducted among Danish, Japanese and Polish companies. These three cultures are different in the scale which presents the level of partnership`s importance (Japan - partnership-focused culture; Poland - middle; Denmark - deal-focused culture). The main result of the presented study shows the differences among companies coming from different cultures in the context of coopetition. Moreover, the results indicate that the cultural context of the researched companies has a bearing on the consequences of their coopetition. (original abstract)